Rise of the Vulcans : the history of Bush's war cabinet - Mann, Jim, 1946- (New York N.Y. : Penguin Books, 2004)
Presents an inside look at George W. Bush's inner circle of foreign policy advisors--Dick Cheney, Donald Rumsfeld, Colin Powell, Paul Wolfowitz, Richard Armitage, and Condoleeza Rice.
A rising politician amid war and dirty tricks -- The intellectual as proteg-- A soldier and a sailor -- Combating the Soviets, Dente and Henry Kissinger -- Enter the Persian Gulf -- Transitions -- Camelot of the conservatives -- Of dictatorships and democracy -- In the midst of Armageddon -- A scandal and its aftermath -- A new republican president, a new foreign policy team -- Use of force -- Death of an empire, birth of a vision -- Vulcans in exile -- A vulcan agenda -- The campaign -- Who runs the Pentagon? -- Warnings and signals -- History starts today -- A new strategy -- Toward war with Iraq.
Originally published : New York : Viking, 2004.
Includes bibliographical references : pages 377-410 and index.
Keywords: Bush, George W. -- 1946- -- Friends and associates; Cabinet officers -- United States -- Biography; Presidents -- United States -- Staff -- Biography; Political consultants -- United States -- Biography; United States -- Foreign relations -- 2001-; United States -- Military policy; United States -- Politics and government -- 2001-2009.